Rodinný dům s provozovnou - Pospíšil, Vojtěch (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Tato bakalářská práce řeší projektovou dokumentaci k provedení rodinného domu s provozovnou. Provozovnou je projekční kancelář pro 1-2 projektanty. Pozemek se nachází v zastavěné části obce Ostrožská Lhota. Pozemek je v mírně svažitém terénu. Rodinný dům je navržen v řadové zástavbě, v proluce, se dvěma nadzemními podlažími a podkrovím. Dům je přístupný z místní komunikace. Objekt je navržen pro 4-5ti člennou rodinu. Vstup do rodinného domu se nachází v 1.NP. Provozovna se nachází v 1.NP a vstup do ní se nachází na stejné straně objetu jako hlavní vstup do domu, na jižní straně objektu. Zastřešení je provedeno sedlovou střechou s vikýři.

This bachelor´s thesis addresses the design documentation for the implementation of a family house with an establishment. Type of business premises is engineer´s office intended for one or two designers. The land is located in the urban area of the municipality Ostrožská Lhota. The land is gently sloping terrain. House is designed in a terraced house in a vacant lot, with two floors and an attic. The house is accessed from the local road. The house is designed for a family of four or five members. The entrance to the house is located in the first floor. business premises is in the first floor and input into it is located on the same side hug as the main entrance to the house on the south side of the building. The roof is made gable roof with dormers.
Family house with an establishment
Keywords: Rodinný dům s provozovnou; projekční kancelář; sedlová střecha; terasa; nadzemní podlaží; obytné podkroví; schodnicové schodiště; průvlak.; Family house with an establishment; engineer´s office; gabled roof; terrace; floor attic; stringer staircase; beam.